Functional group dominance and not productivity drives species richness. (3rd March 2016) - Li, Wenjin; Knops, Johannes M. H.; Brassil, Chad E.; Lu, Junfeng; Qi, Wei; Li, Jinhua; Liu, Minxia; Chang, Shenghua; Li, Wenlong
Abstract : Background : There is a lack of consensus about the productivity–richness relationship, with several recent studies suggesting that it is not productivity but other factors that are the important drivers that determine species richness. Aims : Here, we examine the relationship between productivity, functional group dominance and plant species richness at the plot scale in Tibetan Plateau meadows. These alpine meadows are ideal to examine the species productivity-richness relationship because they have a very high species richness, a large gradient in productivity, and can be dominated by either graminoids (grasses and sedges) or forbs. Methods : We measured plant species richness and above-ground biomass along a natural gradient of functional group abundance in 44 plots distributed across five natural, winter-grazed but otherwise undisturbed sites in the eastern part of the Qing-Hai Tibetan Plateau, in Gansu province, China in 2008. Results : Graminoid abundance (i.e. graminoid biomass as percent of the total above-ground biomass) explained 39% of plot differences in species richness while neither productivity nor the biomass of the three most abundant plant species, either individually or combined, were a significant predictor of species richness. Conclusions : Our results show that within these alpine meadows, a shift from graminoid to forb dominance, rather than the individual dominant species or productivity itself, is strongly correlated with species richness. Thus, differences in functional group abundance can be a strong driver of observed plant species richness patterns.